Good Practices in Health Financing : Lessons from Reforms in Low and Middle-Income Countries - Gottret, Pablo (Washington, DC : World Bank, 2012)
This volume focuses on nine countries that have completed, or are well along in the process of carrying out, major health financing reforms. These countries have significantly expanded their people's health care coverage or maintained such coverage after prolonged political or economic shocks. In doing so, this report seeks to expand the evidence base on good performance in health financing reforms in low- and middle-income countries. The countries chosen for the study were Chile, Colombia, Costa Rica, Estonia, the Kyrgyz Republic, Sri Lanka, Thailand, Tunisia, and Vietnam. With health at the center of global development policy on humanitarian as well as economic and health security grounds, the international community and developing countries are closely focused on scaling up health systems to meet the Millennium Development Goals (MDGs), improving financial protection, and ensuring long-term financing to sustain these gains. With the scaling up of aid, both donors and countries have come to realize that money alone cannot buy health gains or prevent impoverishment due to catastrophic medical bills. This realization has sent policy makers looking for reliable evidence about what works and what does not, but they have found little to guide their search.